PBL-TARL-CRT: INTEGRATING INNOVATIVE APPROACHES TO IMPROVE SCIENCE LEARNING OUTCOMES IN GRADE 8 - Sonya, Mellyaning Oktaviani Sonya Kirana Sari; Harjono, Harjono (BIOMA : Jurnal Ilmiah Biologi, 2024)
This study explores the integration of three innovative learning approaches, namely Problem-Based Learning (PBL), Teaching at the Right Level (TaRL), and Culturally Responsive Teaching (CRT), in improving learning outcomes in Science in grade 8. In education as a pillar of state-building and character-building, these approaches provide a foundation for effective and meaningful learning. PBL places students as agents of learning by providing real challenges, while TaRL adapts learning to students' ability levels, and CRT utilizes students' cultures and experiences for more meaningful learning. An experiment at Junior High School 25 Semarang showed significant improvements in student learning outcomes, learning motivation, and student character. Quantitative analysis confirmed the improvement in learning outcomes, while interviews revealed positive changes in students' learning motivation and character. However, challenges in learning implementation were also shown, including the need to increase diversity in teaching methods, pay attention to students' needs, and create an interactive learning environment. This study shows that the integration of PBL, TaRL, and CRT is promising in improving science learning outcomes and shaping students' characters. However, continuous efforts to improve the quality of learning and the role of teachers are essential to achieving optimal learning goals and creating a bright and characterful generation.